The Impact of Oil Factor on Azerbaijan Economy - Humbatova, Sugra Ingilab; Gasimov, Ragif Kh.; Hajiyev, Natig Gadim-Oglu (International Journal of Energy Economics and Policy, 2019)
The paper examines the role of oil in the world economy and its impact on Azerbaijan economy. The reciprocal relations between factors in research were carried out by differential model of time series and times series have been checked whether they are unit root (Augmented Dickey-Fuller (ADF), Phillips-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) as a methodology of the research. The research focused on the econometric analysis through traditional methods and statistics like EVIEWS 9, GRETL, PASW Statistics. The results confirm that the formation of demand and supply didn't happen in the world market during 15-20 years. The relationships between oil prices and demand and supply prove the novelty of the research. The impact of oil price fluctuations on “economic concept” was high in 2007-2009 and 2014-2016. The practical importance of the article is the employment of the income â€’ generated from “the contract of the century” â€’ for the human development. Keywords: Economic Development, Oil Prices, Econometric Analysis, Functional Dependence, Macroeconomic Indicators JEL Classifications: E31, F31, Q41 DOI: https://doi.org/10.32479/ijeep.8001